Significance of the Geochemistry, Petrogenesis and Tectonic Evolution of the Neoproterozoic amphibolites groups within the Gneisses and Migmatites from El Obeid Area, North Kordofan State, Sudan - Mustafa, Hassan A; Salih, Mushal A; Elmansour, Asim A; Abdelsamad, Mohammed I; Elhadi, Mohammed A; Slama, Einas M (Journal of Advanced Research in Geo Sciences & Remote Sensing, 2021)
El Obeid area consists of a suite of ~1.0 Ga amphibolites that are associated with the gneisses & migmatites. Petrographic and geochemical analyses of these amphibolites indicated that they correspond to basalts that derive from sub-alkaline magmas; and they classiﬁed into two groups. Group A which is cropped out in J. El Eiza’a suffered from weakly anatexis of the first metamorphic event and characterized by low Nb contents (0.44–0.96 ppm), and REE and multi-elemental patterns similar to N-MORB. Group B amphibolites within the gneisses and migmatites in J. Kordofan, only undergone the second metamorphic processes and has high Nb contents ranging from 2.00 to 18.7 ppm, displaying an E-MORB and Pickle Nb-enriched basalt geochemical signature. The low silica and MgO concentrations for the two groups respectively (SiO 2 = 47.8–49.3 and 46.7–50.7 wt %) and (4.40–6.44 and 5.69–7.91%), suggested a mantle source for both groups. Their variable values of La/Ta (15.6–20.3 and 9.20–22.8), La/Nb (1.19–1.96 and 0.91–2.59) and Ba/Nb ratios (13.9–51.9 and 0.70–5.02), respectively, suggesting that they were likely derived from an average melt modified sub-continental lithospheric mantle, also their completely different REE profiles indicated authenticated their heterogeneous mantle source. Both groups have an arc-like and back-arc settings and show inputs of newly subduction-derived melt in the wedge source. Regional relationships indicated that the formation of these rocks resulted from the episodic amalgamation event during that time, an exterior accretion orogeny along the margin of Rodinia during ~1.0 Ga. How to cite this article:  Mustafa HA, Salih MA, Elmansour AA. Significance of the Geochemistry, Petrogenesis and Tectonic Evolution of the Neoproterozoic Amphibolites groups within the Gneisses and Migmatites from El Obeid Area, North Kordofan State, Sudan. J Adv Res Geo Sci Rem Sens 2020; 7(3&4): 1-20.